The erosion kinetics of conventional and resin-modified glass-ionomer luting cements in acidic buffer solutions - Hazar-Yoruc, Binnaz; Bavbek, Andac Barkin; Ozcan, Mutlu (JAPANESE SOC DENTAL MATERIALS DEVICES, 2012)
This study investigated the erosion kinetics of conventional and resin-modified glass-ionomer luting cements in acidic buffer solutions as a function of time. Disc shaped specimens were prepared from conventional (Ketac-Cem: KTC) and resin-modified glass ionomer cements (Fuji Plus: FP) and immersed in three acidic buffer solutions (0.01 M) namely, acetic acid/sodium acetate (AA), lactic acid/sodium lactate (LAB) and citric acid/sodium citrate (CAB) with a constant pH of 4.1 and stored for 1, 8, 24, 48, 80, 120 and 168 h. F concentration was determined using ion-specific electrode. Si, Ca and Al concentrations were determined by atomic absorption spectroscopy. Ca, Al, Si and F solubility rates in both FP and KTC were the highest in CAB solution. The erosion rates of both FP and KTC in all buffer solutions increased as a function of immersion time. The amount of F eluted from FP was more than that of KTC. The total amount of elements released from FP was less than KTC in all solutions.
Keywords: Acidic buffer solutions; Erosion; Glass-ionomer cement; Resin-modified glass-ionomer cement; Solubility; COMPOSITE RESIN; PHYSICAL-PROPERTIES; WATER-ABSORPTION; ION-RELEASE; PH; ROUGHNESS; MECHANISM; FLUORIDE; ENAMEL; Dentistry, Oral Surgery & Medicine; Materials Science